Analysis Of The Effectiveness Of Distribution Of Zakat Funds By The Baitul Maal PLN Foundation (YBM PLN) - Rahmad Ridho Zeen; Nurhayati Nurhayati (Pusat Riset dan Inovasi Nasional, 2023)
It is obligatory for everyone who is economically capable to give zakat, not only as a form of sympathy for someone's situation but also to protect them from famine or other disasters. Zakat is one of the most important factors in eradicating poverty which is a source of disaster for both individuals and society. therefore in Islam it is obligatory to give zakat to people who are able in accordance with the word of Allah SWT.